Historia de los Papas desde fines de la Edad Media En la época de la monarquía absoluta - PASTOR, Ludovico (G.GILI, 1950)
Contenido : ALEJANDRO VII; 1655-1667; CLEMENTE IX; 1667-1669; CLEMENTE X; 1670-1676